DEIKSIS WAKTU DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE - Namira Anjani; Sainil Amral (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
The study describes the temporal deixis of past, present, and future in the novel “Si Anak Badai” by Tere Liye. This type of research is qualitative research with a naturalistic research method. The primary data was drawn from words, sentences, and quotations containing the temporal deixis in Tere Liye's novel “Si Anak Badai”. At the same time, secondary data was obtained from literature related to deixis. The research results obtained in the novel “Si Anak Badai” by Tere Liye consisted of 119 quotes of deixis by using Yule's preassumption theory. The form of deixis of the past was found as many as forty quotations consisting of nineteen temporal deixes of the past lalu, thirteen quotes of deixis kemarin, and eight quotations of the deixis tadi. The temporal deixis of the present is found as forty-six quotations consisting of forty-two deixis of time ini, one deixis of time itu, and three quotes of deixis sekarang. The form of future temporal deixis is found as thirty-three consist of twenty-four quotes of temporal deixis besok, two future deixes of depan, one deixis of kemudian, one deixis of time lusa, and five deixes of time nanti. Keywords: temporal deixis, novel, Si Anak Badai